ANGSA DALAM KARYA TAPESTRI - Lourena Tessa Maharani; Erwin Erwin (Universitas Negeri Padang, 2020)
Swan have form/anatomy that interesting ang beautiful. Swan also made embodient symbol affection, and loyality, baecause the excess is that interesting to made inspirtion in tapestry work. Throug this tapestry technique generate 7 work tittle: Flying Formation; Eat; Partner Seizing; In Pairs; Loyality; Protection; First Lesson. Recomended to sense/work, next to explore the moment life other swan.Keywords : Swan, Tapestry